Israeli Colonial Governance vs. Palestinian Resistance: An Institutional Genealogy - Hani Awad (575131) (2023)
This article examines the institutional genealogy of Israeli colonial governance (ICG) and the accompanying patterns of Palestinian resistance in the occupied West Bank and Gaza Strip. It argues that ICG has experienced three phases, each marked by a particular form of direct or indirect colonial rule. Each of these colonial rule forms has been resisted through a distinct pattern of centralized or decentralized collective political agency. I argue that both the form and governing logic of ICG are determined not only by colonialist aims, but also by their interplay with the Palestinian resistance. Other Information Published in: Middle East Critique License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/19436149.2023.2229678